2022
DOI: 10.1016/j.clnesp.2021.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of micronutrient supplements in patients with coronavirus disease 2019: A comprehensive systematic review and meta-analysis

Abstract: Background and aims Micronutrient supplements such as vitamin D, vitamin C, and zinc have been used in managing viral illnesses. However, the clinical significance of these individual micronutrients in patients with Coronavirus disease 2019 (COVID-19) remains unclear. We conducted this meta-analysis to provide a quantitative assessment of the clinical significance of these individual micronutrients in COVID-19. Methods We performed a comprehensive literature search usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 48 publications
(81 reference statements)
3
48
3
Order By: Relevance
“…However, there is no specific dose associated with a better prognosis. A meta-analysis revealed heterogeneity in doses and administration of these micronutrients and no significant effect on mortality but the various effect on the need for intubation and length of stay [ 14 ]. Moreover, micronutrient supplementation is not free from side effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no specific dose associated with a better prognosis. A meta-analysis revealed heterogeneity in doses and administration of these micronutrients and no significant effect on mortality but the various effect on the need for intubation and length of stay [ 14 ]. Moreover, micronutrient supplementation is not free from side effects.…”
Section: Introductionmentioning
confidence: 99%
“…In viral infections, including COVID-19, the positive effect of VC administration has also been reported [ 135 , 136 , 137 , 138 , 203 , 209 ]. The neutral effect of VC has been mentioned in the case of patients with COVID-19 in a few publications [ 47 , 48 , 190 , 191 , 192 , 193 , 194 , 196 , 198 , 199 , 200 ], and the adverse effects of the administration of high doses of VC have been mentioned as an aspect of urinary and kidney stones [ 88 , 89 , 90 ] and nephropathy [ 45 ]. These last effects were found to be neutral.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to oral supplements, a systematic review of 12 randomized controlled trials on use of dietary herbal supplements to increase micronutrient provision [111] showed that high risk of bias makes it difficult to interpret results; the authors conclude that some promising effects were suggested in improving recovery, and zinc supplements could lead to faster recovery from olfactory dysfunction. A meta-analysis focusing on vitamin C, vitamin D and zinc reported beneficial effects of vitamin D supplementation in reducing risk of intubation during COVID-19 illness, whereas no significant impact was detected for vitamin C and zinc on mortality, intubation risk and length of hospital stay [112].…”
Section: Benefits: Acute Setting (Hospital and Icu)mentioning
confidence: 97%